2022
DOI: 10.1186/s40359-022-00971-w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of stress, personality and coping on learning motivation and mental health in university students during a pandemic

Abstract: The aims explored the associations between stress, personality and coping on student mental health and compared defensive-pessimism and optimism as influences on learning motivation. Most research construes ‘stress’ as ‘distress’, with little attempt to measure the stress that enhances motivation and wellbeing. Undergraduate psychology students (N = 162) were surveyed on student and pandemic-related stressors, personality, support, control, mental health and learning motivation. Overall, adverse mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Gibbons (2022b) found that teaching and course demands, along with a range of support -from peers, tutors, the wider university and one's partner, when rated as a hassle, were higher in those 'at risk' of a stress-related illness. The support ratings were also associated with lower course satisfaction and higher anxiety (Gibbons, 2022b(Gibbons, , 2022c. Personal sources of stress include nancial concerns, managing free time, working part-time while studying, and future concerns (Gibbons, 2015).…”
Section: Sources Of Student Stressmentioning
confidence: 95%
See 4 more Smart Citations
“…Gibbons (2022b) found that teaching and course demands, along with a range of support -from peers, tutors, the wider university and one's partner, when rated as a hassle, were higher in those 'at risk' of a stress-related illness. The support ratings were also associated with lower course satisfaction and higher anxiety (Gibbons, 2022b(Gibbons, , 2022c. Personal sources of stress include nancial concerns, managing free time, working part-time while studying, and future concerns (Gibbons, 2015).…”
Section: Sources Of Student Stressmentioning
confidence: 95%
“…Sources of student stress include academic demands, such as coursework, exams and work-life balance (Ansari, Oskrochi & Haghgoo, 2014, Gibbons, 2022a, 2022b; fear of failure, lack of timely feedback and the quality of teaching (Gibbons, 2008(Gibbons, , 2010(Gibbons, , 2015. Gibbons (2022b) found that teaching and course demands, along with a range of support -from peers, tutors, the wider university and one's partner, when rated as a hassle, were higher in those 'at risk' of a stress-related illness. The support ratings were also associated with lower course satisfaction and higher anxiety (Gibbons, 2022b(Gibbons, , 2022c.…”
Section: Sources Of Student Stressmentioning
confidence: 99%
See 3 more Smart Citations